Aflatoxin awareness and Aflasafe adoption potential of Nigerian smallholder maize farmers - Johnson, A.M.; Fulton, J.R.; Abdoulaye, Tahirou; Ayedun, B.; Widmar, N.J.O.; Akande, A.; Bandyopadhyay, Ranajit; Manyong, Victor (Brill, 2018)
Aflatoxin is a potent mycotoxin that can cause cancer and death and is associated with stunted growth. Prevalence of aflatoxin is widespread in Africa negatively impacting health and trade. Aflasafe is a biological control product that can be applied to maize or groundnut fields to reduce aflatoxin contamination. This study examines the levels of aflatoxin and Aflasafe awareness and understanding among smallholder maize farmers in Nigeria. In addition, the factors affecting Aflasafe purchase patterns and sustained usage over multiple growing seasons by farmers were evaluated. In-person surveys of 902 Nigerian smallholder farmers were conducted during October and November of 2016. This work contributes to the existing literature by documenting awareness levels of aflatoxin and use of Aflasafe as a control in Nigeria. Results suggest that the level of awareness of aflatoxin was very high in states where Aflasafe was promoted as an intervention for aflatoxin management. In Kaduna state, the region with the longest intervention, there was a consistent increase in the usage of Aflasafe since its introduction in 2010. Furthermore, farmers who purchase Aflasafe bundled (combined) with other inputs were more likely to persist in using the product. Education was found to significantly and positively impact continued usage of Aflasafe. Continued interventions, promotion and general education of the public are recommended for increased awareness, trial, and adoption of Aflasafe in Nigeria.